SMARTnatomy CARDIO MOBILE APPLICATION FOR IMPROVEMENT IN EFFECTIVENESS OF ANATOMY LEARNING MEDIA - Bakti, Alfonsus Aryo Sunu; Hastami, Yunia; Munawaroh, Siti; Wiyono, Nanang (Universitas Gadjah Mada, 2023)
Background: Anatomy is an important science to know how the body works, the relationship between body structures that change due to disease, as well as the basis for medical students to carry out physical examinations on patients. Currently, students perceive anatomy as a difficult science. Therefore, an anatomy learning method with more effective learning media is needed. The purpose of this study is to determine the difference in the effectiveness of the SMARTnatomy Cardio mobile application with the atlas for medical students.Methods: This research is a quasi-experimental study with equivalent control group design which is conducted at the Faculty of Medicine, Sebelas Maret University, Surakarta. The sample of this study are 66 medical students who were taken by purposive sampling technique. Independent variable is the SMARTnatomy Cardio mobile application and anatomy atlas. The dependent variable is effectiveness of anatomy learning media. The data obtained are pretest, posttest, and grade increases. The data are then calculated using SPSS software and analyzed using the Mann Whitney U-Test and Wilcoxon Test.Results: Test results show anatomy atlas and the SMARTnatomy Cardio mobile application are equally effective as anatomy learning media (p = 0.000). However, there is a significant difference in post test scores (p = 0.035) where anatomy atlas is slightly more effective than SMARTnatomy Cardio mobile application (p = 0.017).Conclusion: There is a difference in the effectiveness of the SMARTnatomy Cardio mobile application with the atlas for medical students.